COMMUNITY EDUCATION PROGRAM REGARDING TUBERCULOSIS AND NUTRITIONAL ASSISTANCE AND PSYCHOSOCIAL SUPPORT FOR TUBERCULOSIS PATIENTS - Ika Krisnawati, Dyah; Khafid, Muhamad (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Tuberculosis (TB) remains a significant public health problem in Indonesia. Sembayat Village, located in Manyar District, Gresik Regency, East Java, is one of 23 villages in the district. Currently, 1 active TB patient has been found in RT 22 RW 02. Seeing the densely populated situation, it is possible that the disease will spread if preventive measures are not taken immediately. Psychosocial assistance is also needed for patients and families considering that this disease requires relatively long treatment and must be completed. We divide this Community Service Activity into several stages of activity. The first stage is the preparation stage. Community service activities were carried out on Thursday, May 8, 2025, starting at 09.00 - 12.00. The activities carried out were counseling on TB (Definition, signs and symptoms, treatment, prevention), Healthy lifestyles to increase immunity, and good nutrition to stay healthy. In addition, there was a symbolic handover of the TB Guidebook for the Community and distribution of basic necessities to families of TB patients. On the evaluation stage, the community was very enthusiastic about asking questions, this proved that the community understood what was explained during the counseling.